A silver(I) coordination polymer with bridging bis(thiosemicarbazone) ligands and unsupported argentophilic interactions. Issue 11 (28th October 2022) - Crouch, Sophie A.; Davey, Patrick R.W.J.; Forsyth, Craig M.; Batten, Stuart R.; Paterson, Brett M.
Abstract: The synthesis and structural characterization of a silver(I) coordination polymer is reported. The structure contains a silver(I) ion coordinated by three sulfur donor atoms from three bridging bis(thiosemicarbazone) ligands in a trigonal planar coordination environment, generating a 2-D coordination polymer. The structure involves hydrogen bonds between the tetrafluoroborate counterion and the ligands and close Ag⋅⋅⋅Ag contacts to create an overall 3-D network. Graphical Abstract: UF0001